Abiotic and biotic-controlled nanomaterial formation pathways within the Earth’s nanomaterial cycle - Michael Schindler; Jie Xu; Michael F. Hochella (Communications Earth & Environment)
Abstract Nanomaterials have unique properties and play critical roles in the budget, cycling, and chemical processing of elements on Earth. An understanding of the cycling of nanomaterials can be greatly improved if the pathways of their formation are clearly recognized and understood. Here, we show that nanomaterial formation pathways mediated by aqueous fluids can be grouped into four major categories, abiotic and biotic processes coupled and decoupled from weathering processes. These can be subdivided in 18 subcategories relevant to the critical zone, and environments such as ocean hydrothermal vents and the upper mantle. Similarly, pathways in the gas phase such as volcanic fumaroles, wildfires and particle formation in the stratosphere and troposphere can be grouped into two major groups and five subcategories. In the most fundamental sense, both aqueous-fluid and gaseous pathways provide an understanding of the formation of all minerals which are inherently based on nanoscale precursors and reactions.